(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Glimepiride, oral sulfonyl urea, BCS class-II drug is used to treat diabetes (type-II). Due to its low solubility, it is an ideal candidate for solubility enhancement, leading to better bioavailability and subsequent dose. In the present study, the solid dispersion technique was used to improve the solubility using solvent evaporation method. The solid dispersions were prepared using affnisol 912 as a solubility enhancer. The prepared solid dispersions were evaluated for solubility in 0.1N HCl pH 1.2 and phosphate buffer pH 7.8 medium. The solubility of glimepiride in optimized solid dispersion (SD1) formulation was 682.44 μg/mL compared to 6.88 μg/mL for pure drug in pH 7.8 medium. The solid dispersion (SD1) was further formulated into the tablets. The gastro-retentive and mucoadhesive properties were contributed to the tablets by HPMC K4M and Carbopol 940, respectively. Factorial design (Central composite design) was used to optimize the gastro-retentive tablets. The tablet formulations showed good mucoadhesive properties and drug release up to 12 hours in pH 1.2 with 0.5% SLS medium. The optimized formulation (F2) showed cumulative drug release up to 97.20 ± 0.99% in 12 hours. The drug release kinetics also showed that the drug is release by dissolution and diffusion from the drug matrix. The gastro-retention studies in rabbits also showed the tablets remain within the GIT up to 12 hours as confirmed by x-ray images.